Solid Waste Management in Lagos State, Nigeria: Evaluating the Environmental Impact and Policy Effectiveness of Waste-To-Energy Initiatives - Ajulor, Omoniyi Victor; Ibikunle, Busayo Qazeem; Fajonyomi, Sylvester Olubanji (Journal of Environmental and Energy Economics, 2024)
The study examined the effectiveness of the solid waste management policy on environmental hazard and waste to energy initiatives in Lagos State, Nigeria. In line with the objectives of the study, two hypotheses were formulated. Primary and secondary data were sourced for the study. For the primary data, A survey was carried out and a structured questionnaire was used to generate information from Lagos State Ministry of Environment and Water Resources; Lagos State Waste Management Authority (LAWMA); Lagos State Environmental Protection Agency (LASEPA); Private Sector Partners (PSPs); Lagos Recycler Association (LAGRA) and selected representatives of the end-users across the 20 local governments and 37 Local Community Development Areas (LCDAs) in Lagos State. Regression analysis and Pearson coefficient correlation were used to test the hypotheses. All the data generated were processed through the use of Statistical Package for Social Sciences (SPSS). Key informant interviews (KII) and focused group discussions (FGD) were also conducted. For the second data, information was sourced from the library, textbooks, journal articles, bulletins, the internet and policy documents. The findings of the study revealed that: solid waste disposal has a significant effect on environmental hazard reduction strategy on air pollution management in Lagos State, Nigeria; the incessant in hazard and secondly, a significant effect exists between solid waste management policy and waste-to-energy initiative. The study therefore concluded, among others that building an institutional capacity to support the waste-to-wealth and waste-to-energy initiative for effective solid waste management are driving force for promoting the Gross Domestic Product (GDP) of Lagos State. The government also needs to create public orientation on the need for environmental hygiene and waste disposal techniques to reduce environmental hazards and infectious diseases that may affect the plan of the state to become a mega-city.